Oral health changes among Indigenous and non‐Indigenous Australians: findings from two national oral health surveys. Issue Volume 66:Issue Supplement 1(2021) (11th May 2021) - Jamieson, L; Do, L; Kapellas, K; Chrisopoulos, S; Luzzi, L; Brennan, D; Ju, X
Abstract: Background: Historically, Indigenous Australians experienced poorer oral health than non‐Indigenous Australians. We aimed to ascertain if Indigenous Australian oral health improved relative to non‐Indigenous oral health between the 2004‐06 and 2017‐18 National Surveys of Adult Oral Health (NSAOH). Methods: Both NSAOHs were population‐based cross‐sectional surveys of Australian adults aged 15 years or more. In both surveys, representative samples of adults were drawn through a three‐stage, stratified sample design within metropolitan and regional areas in each state/territory. Frequencies of Indigenous and non‐Indigenous self‐reported and clinical oral health variables were ascertained, and differences were calculated between the 2004‐06 and 2017‐18 NSAOHs. Ninety‐five per cent confidence intervals were calculated and weights were used to account for the complex sampling methodology of both surveys. Results: In 2004‐06, 229 Indigenous and 13 882 non‐Indigenous Australians provided self‐report data, and 87 and 5418 of these had dental examinations, respectively. In 2017‐18, 334 Indigenous and 15 392 non‐Indigenous Australians provided self‐report data, and 84 and 4937 of them had dental examinations respectively. Between the surveys, relative to their non‐Indigenous counterparts, Indigenous Australians experienced greater levels of: inadequate dentition (4.2%), experience of toothache (4.8%), problem‐based dental attendance (4.5%) and 1+ teeth decayed, missing or filled (4.4%). Conclusions: The gap between poor self‐reported and clinical oral health between Indigenous and non‐Indigenous Australians was greater in the more recent survey.